2020
DOI: 10.1186/s13071-020-04371-0
|View full text |Cite
|
Sign up to set email alerts
|

Rapid detection of Galba truncatula in water sources on pasture-land using loop-mediated isothermal amplification for control of trematode infections

Abstract: Background Fascioliasis caused by the trematodes Fasciola hepatica and F. gigantica, is a global neglected zoonotic disease estimated to cost the livestock industry over €2.5 billion annually. Farm management measures and sustainable use of anthelmintics can, in principle, effectively control trematode infection in livestock and reduce the rate of developing anthelmintic resistance. Previously, we designed an environmental DNA (eDNA) assay to identify a common trematode intermediate host, the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 57 publications
0
18
0
Order By: Relevance
“…Advances have been made in using LAMP assays to process environmental samples such as hive debris 24 and water samples 23 , 25 , 26 . Three of the LAMP studies based on eDNA detection in water samples were targeted at mussel species from the Dreissena genus 23 , 26 , and one was developed to detect the presence of a parasite’s intermediate host (a snail species) in drinking spots for livestock 25 . The coupling of eDNA sampling with a LAMP detection approach was thus proven operational.…”
Section: Introductionmentioning
confidence: 99%
“…Advances have been made in using LAMP assays to process environmental samples such as hive debris 24 and water samples 23 , 25 , 26 . Three of the LAMP studies based on eDNA detection in water samples were targeted at mussel species from the Dreissena genus 23 , 26 , and one was developed to detect the presence of a parasite’s intermediate host (a snail species) in drinking spots for livestock 25 . The coupling of eDNA sampling with a LAMP detection approach was thus proven operational.…”
Section: Introductionmentioning
confidence: 99%
“…All filters, including blank controls, were homogenized using a sterile pipette tip with each whole filter subjected to DNA extraction via the PowerSoil® kit protocol. PCR targeting a 288 bp strand of the G. truncatula ITS2 gene and gel electrophoresis were used to identify G. truncatula eDNA in extracts as previously described by Jones et al (2018) with the modifications stated by Davis et al (2020). The limit of detection of this PCR assay is 0.5 pg μL −1 (Davis et al, 2020) and the assay has been shown to be capable of detecting G. truncatula eDNA in 100% of habitats where the snail was surveyed (Jones et al, 2018).…”
Section: Study Design and Edna Analysismentioning
confidence: 99%
“…In recent years, eDNA capture and detection protocols have been developed to detect intermediate snail host eDNA, including that of Galba truncatula (Jones et al, 2018;Davis et al, 2020), Austropeplea tomentosa (Rathinasamy et al, 2018;Rathinasamy et al, 2021), Oncomelania hupensis (Fornillos et al, 2019) and Bulinus truncatus (Mulero et al, 2020). As these snails are often present at low densities and are difficult to find and differentiate from non-intermediate host snails, eDNA surveys can outperform traditional physical detection methods (Jones et al, 2018) as has been shown for other organisms (Wilcox et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Zumaquero-Ríos et al ., 2013; Alba et al ., 2016). Furthermore, other types of samples beyond blood, stool (definitive host) and snails (intermediate host) have been added to the panel of possibilities for active screening; from meat juice and bulk milk for serological assessment in livestock (Charlier et al ., 2009; Villa-Mancera and Reynoso-Palomar, 2019) to water for environmental DNA detection of the parasite and its snail hosts (Jones et al ., 2018; Davis et al ., 2020).…”
Section: Scientific and Political Factors: Changing The View From Spomentioning
confidence: 99%